Flipped Classroom Teaching Model: It’s Effect on Students English Achievement and Engagement - Halad Hulwana Hulwana (ELITE Association Indonesia, 2022)
There has been lot of studies that already investigated the application of flipped classroom teaching model on students’ achievement of several subjects. However, not many were trying to identify its effect on achievement and engagement at the same time. This study was aimed at identifying the effect of flipped classroom model both on achievement and engagement. This research involved two groups of students of a Junior High School, one for the experimental class and the other for control class. The student achievement was analyzed by doing pretest and posttest, examined using t-test and students’ engagement was examined using an instrument of Classroom Engagement Inventory. Finally, it was found that Flipped Classroom model has significant effect on students’ achievement and Students’ Engagement. Keywords: Flipped classroom, Students’ English Achievement, Students’ Engagement